Transcriptome Analysis of Porcine Liver Reveals Hepatoprotective Mechanisms of Dietary Curcuma Longa Extract Supplementation against Aflatoxin B1: A Single-Cell RNA Sequencing Perspective - purohit, Nihal (Translational Research in Veterinary Science, 2026)
Aflatoxin B1 (AFB1), a potent mycotoxin produced by Aspergillus species, poses significant threats to livestock health and food safety, particularly in swine production. AFB1-induced hepatotoxicity involves complex molecular mechanisms including cytochrome P450-mediated bioactivation, oxidative stress, inflammatory responses, and disrupted cellular homeostasis. Dietary supplementation with Curcuma longa extract (curcumin) has emerged as a promising hepatoprotective intervention, demonstrating efficacy through multiple molecular pathways including inhibition of phase-I bioactivation, activation of Nrf2-driven antioxidant responses, anti-inflammatory effects, and restoration of autophagy. While bulk transcriptomic studies in porcine models have revealed broad gene expression changes, single-cell RNA sequencing (scRNA-seq) offers unprecedented resolution to dissect cell-type-specific responses in the heterogeneous liver microenvironment. This review synthesizes current evidence on AFB1 hepatotoxicity mechanisms, curcumin's hepatoprotective pathways, and the transformative potential of scRNA-seq technology to resolve cellular heterogeneity in porcine liver responses to mycotoxin exposure and dietary intervention. We highlight the critical role of porcine-specific cytochrome P450 2A19 in AFB1 bioactivation, intercellular communication via extracellular vesicles in fibrogenesis, and the methodological advances enabling single-cell transcriptomic in primary porcine hepatocytes. This synthesis provides a roadmap for future scRNA-seq studies to definitively map cell-type-specific protective mechanisms of curcumin against AFB1 hepatotoxicity in swine.